Infrared tomography : data distribution system for real-time mass flow rate measurement - Abdul Rahim, Ruzairi; Pang, Jon Fea; Chan, Kok San; Leong, Lai Chen; Rahiman, Mohd. Hafiz Fazalul (International Frequency Sensors Association (IFSA), 2007)
The system developed in this research has the objective of measuring mass flow rate in an online mode. If a single computer is used as data processing unit, a longer time is needed to produce a measurement result. In the research carried out by previous researcher shows about 11.2 seconds is needed to obtain one mass flow rate result in the offline mode (using offline data). This insufficient real-time result will cause problems in a feedback control process when applying the system on industrial plants. To increase the refreshing rate of the measurement result, an investigation on a data distribution system is performed to replace the existing data processing unit.